Hypoxic mesenchymal stem cell-derived secretome and alkaline water synergistically reduce apoptosis and insulin resistance in type 2 diabetes mellitus rat model - Melisa Septi Mawarini; Eko Setiawan; Agung Putra (Faculty of Medicine, Universitas Trisakti, 2025)
BACKGROUNDType 2 Diabetes Mellitus (T2DM) is characterized by chronic inflammation and insulin resistance. These factors contribute to pancreatic β-cell apoptosis, reducing insulin production and impairing glucose homeostasis. This study aims to evaluate the protective effects of hypoxic mesenchymal stem cell-derived secretome (HMSCS) and alkaline water on inflammation, apoptosis, and insulin resistance in a T2DM rat model. METHODSAn experimental study was conducted involving 24 male Wistar T2DM model rats (aged 6-8 weeks, 200-250g). They were randomized into four groups: T2DM rats only as negative control (K-), T2DM rats with metformin as positive control (K+), HMSCS treatment (P1), and HMSCS plus alkaline water group (P2). Caspase-3 expression was measured to assess apoptosis levels using RT-PCR, while homeostatic model assessment for insulin resistance (HOMA-IR) was measured using ELISA. One way ANOVA followed by a post hoc LSD test were used to analyse the data. RESULTSThe P1 group (3.03 ± 1.26 a.u) and P2 group (2.93 ± 0.52 a.u.) had significantly lower caspase-3 expression compared to K- group (6.66 ± 2.76 a.u.) (p<0.05), but were not significantly different from K+ group (3.83 ± 1.61 a.u.) (p>0.05). Additionally, P2 group (6.76 ± 0.96) had a significantly lower HOMA-IR than K- group (18.92 ± 2.63) and K+ group (10.85 ± 1.39) (p<0.05), and similarly the P1 (7.71 ± 0.53) group also showed significant difference from K- and K+ groups (p<0.05). CONCLUSIONHigher doses of HMSCS and alkaline water are associated with reduced pancreatic β-cell apoptosis and improved insulin sensitivity, highlighting its potential as a novel therapeutic approach for T2DM.